PENEGAKAN HUKUM TERHADAP PELAKU KEKERASAN FISIK DALAM RUMAH TANGGA - Nugraha, Ahmad Angga; Harahap, Irawan; Pardede, Rudi (The Juris, 2025)
This includes physical assaults, including actions against minors such as slapping, or more severe acts involving deadly weapons. Furthermore, physical violence may involve hitting, injuring the body with blunt objects, sharp weapons, or other technology-related means (e.g., electricity). The use of violence may cause various injuries such as bruises, stab wounds, lacerations, or even injuries that lead to death. Threats or acts of violence can occur directly, through speech, body language, or indirectly (via letters, phone calls, or third parties) with the intent of using physical force against another person. The purpose of this research is To analyze the enforcement of the law against perpetrators of physical domestic violence based on Law No. 23 of 2004 on the Elimination of Domestic Violence in the jurisdiction of the Pekanbaru Police Resort; To examine the legal process and effectiveness in the handling of physical domestic violence cases; To identify efforts to overcome obstacles in enforcing the law against perpetrators of physical domestic violence in the same jurisdiction. This study employs a sociological legal research method. Based on the research findings, it is known that the enforcement of the law against perpetrators of physical domestic violence in accordance with Law No. 23 of 2004 in the jurisdiction of the Pekanbaru Police Resort has not been running effectively. This is evident from the continued prevalence of domestic violence cases in society. The persistent occurrence of domestic violence reflects the fact that the law has not yet been fully felt by victims—especially women and children, who are most vulnerable to abuse. One of the fundamental underlying issues behind weak law enforcement in domestic violence cases is the strong influence of patriarchal culture embedded in the social structure. In a patriarchal system, men are positioned as the dominant authority in the household, while women are expected to be obedient and submissive.